Analysis of the Frequency-Based Relationship between Inflation Expectations and Gold Returns in Turkey - Remzi Gök; Aviral Kumar Tiwari (Istanbul Business Research)
This paper explores the relationship between inflation expectations and gold returns of monthly and annual maturities in Turkey from 2006 to 2020 with 177 monthly observations through the application of wavelet cohesion and causality tests. The findings reveal significantly negative cohesion in the short term and significantly positive cohesion in the long term, indicating that the hedging ability of gold prices exists only in the long term during crisis periods. Therefore, the findings provide evidence for the validity of the expected inflation effect hypothesis in Turkey. The ordinary least squares results, on the other hand, show that the ongoing COVID-19 pandemic is the most prominent factor in the movement of inflation and gold at all wavelet scales for the two types of maturities. The continuous wavelet transformation based Granger-causality test provides little evidence for out-of-phase and unidirectional causality running from the inflation expectations to gold returns in the higher and medium frequency bands. Furthermore, the QQR results show an asymmetrical impact on each other—implying a hedging effectiveness of gold against inflation expectations—and reveal that its size and magnitude change significantly under different economic conditions and data frequencies. The results have significant implications for portfolio and risk management during normal market conditions as well as hedging and speculation activities during crises in short term and long term periods, respectively.